(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2018)
The study was undertaken on insect, mite and nematode species diversity in Bangladesh Tea Research Institute (BTRI) main farm, Baraoora and Phulcherra tea estates in Sreemangal, Bangladesh from the period of 2014 to 2015. The study was done through direct field observations, sweeping net, food trap, sticky trap, light trap and Baermann Funnel method. A total of 71 insect, mite and nematode species was recorded belonging to 45 families under 14 orders. Among these, 25.35% species were foliar insects and mites, 26.76% soil insects and nematodes, 21.13% beneficial insects and 26.76% butterflies. All the foliar and soil insects, mites and nematodes were found as recognized pests of tea. The highest number of individuals among foliar pest was the red spider mite (Oligonychus coffeae) and the lowest number was the coffee red borer (Zeuzera coffeae). Of the soil pests, 77.47% species were termites, 14.33% nematodes, 4.86% field cricket, 2.63% mole cricket and 0.72% cockchafer grub. Regarding the soil pests, live wood termite (Microtermes obesi) was the highest and dagger nematode (Xiphinema sp.) was the lowest in number. One species of foliar insect, looper caterpillar (Hyposidra infixaria) and three species of nematodes, viz. reniform nematode (Rotylenchulus sp.), ring nematode (Criconemoides sp.) and dagger nematode (Xiphinema sp.) were recorded for the first time as tea pest in Bangladesh. In case of beneficial insects, 81.49% species were predators, 16.73% parasitoids and 1.78% parasites. Lady bird beetle (Micraspis discolor) was the highest in number and anthocorids (Anthocoris sp.) were the lowest. Nineteen species of butterflies were found. Of the observed butterflies, lemon emigrant (Catopsilia pomona) was the highest and large oakblue (Arhopala amantes) was the lowest in number. According to pest status, tea mosquito bug, red spider mite, thrips, looper caterpillar, live wood termites, root knot nematode and root lesion nematode were major, and the rest of those were occasionally regarded as minor pest. The population of most of the pest species was higher in peak cropping season (April-November), whereas the lowest population was recorded in off season (December-February). According to diversity indices, the diversity of foliar pest was higher than the other groups and the foliar pest was more evenly distributed in comparison to soil, beneficial insects and butterflies. J. Biodivers. Conserv. Bioresour. Manag. 2017, 3(1): 31-44